Influence of mechanical activation on microstructure and crystal structure of sintered MgO-TiO2 system - Filipović S.; Obradović N.; Pavlović V.B.; Marković S.; Mitrić M.; Ristić M.M. (Science of Sintering, 2010)
Mixtures of MgO-TiO2 were mechanically activated using high-energy planetary ball mill during 5, 10, 20, 40, 80 and 120 minutes. Sintering process was preformed in air at 1100o-1400oC for 2h. The decrease in powder’s particle size was noticed as the time of mechanical activation increased and confirmed by particle size analyzer. XRD analyses were performed in order to acquire the information about phase composition. Different ratio mixtures of MgTiO3 and Mg2TiO4 are present within all sintered samples. The effect of tribophysical activation on microstructure was investigated by scanning electron microscopy. The differential thermal gravimetric analysis has been performed in order to investigate thermal behaviour of the mixtures.